Self-Actualization in Main Character’s Life Journey in "The Bell Jar" (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
Self-actualization is term that is commonly used in psychology theories. The term can be simply translated as the full realization of someone’s potential or true self. This study was conducted to analyze the life journey of the main character of The Bell Jar in achieving herself-actualization. The purposes of this study are to describe the character of the main character in The Bell Jar and to describe the main character in achieving self-actualization and how it is portrayed in the novel. This study was done using a descriptive qualitative method and using Maslow's Hierarchy of Human Needs theory and New Criticism theory to explain the main character and her journey in achieving self-actualization in the form of words. The object of the study was the novel The Bell Jar and this study focused on Esther Greenwood as the main character. List of an observational sheet was used as the research instrument and the data was taken through library research. The analysis was conducted by interpreting Esther’s utterances and actions using New Criticism theory to describe Esther’s characterization and Maslow’s Hierarchy of Human Needs theory to describe Esther’s self-actualization. The study results showed that Esther’s self-actualization is the results of her being able to fulfill her previous stages both directly and indirectly before reaching self-actualization stage along her life journey. Keywords: Characterization, Hierarchy of Human Needs, Life Journey, New Criticism, Self-actualization